Effectiveness of tacrolimus in comparison with methotrexate or biologics in propensity score-matched patients with rheumatoid arthritis. Issue 6 (1st November 2016) - Nakajima, Ayako; Inoue, Eisuke; Taniguchi, Atsuo; Momohara, Shigeki; Yamanaka, Hisashi
Abstract: Objective : To analyze the effectiveness of tacrolimus (TAC) in comparison with methotrexate (MTX) or biologics in propensity score (PS)-matched rheumatoid arthritis (RA) patients. Methods : RA patients with moderate or high disease activity as defined by the 28-joint disease activity score (DAS28) and who had completed at least two successive biannual RA cohort surveys were analyzed. Patients were assigned in a stepwise fashion to one of four groups (Biologics, MTX, TAC, or Control) according to medication changes during a 6-month period. A PS was generated for each of three conditions (Biologics, MTX or Control group versus the TAC group, respectively), followed by the assignment of PS-matched patients. At 1 year, the DAS28 in each treatment versus TAC group was analyzed using a mixed effect model with repeated measures. Results : Compared with the respective PS-matched TAC group, the difference in DAS28 at 1 year was −0.398 [95% confidence interval (CI) − 0.660 to −0.136, p  < 0.005] in the Biologics group ( N  = 120),  −0.045 (95% CI −0.222 to 0.133, p  = 0.622) in the MTX group ( N  = 465), and 0.182 (95% CI 0.010 to 0.353, p  < 0.05) in the Control group ( N  = 462). Conclusion : TAC may provide a potential therapeutic option for RA patients with moderate to high disease activity.